Progress in research on the role of fluoride in immune damage - Zhu, Siqi; Wei, Wei (Frontiers in Immunology, 2024)
Excessive fluoride intake from residential environments may affect multiple tissues and organs; however, the specific pathogenic mechanisms are unclear.Researchers have recently focused on the damaging effects of fluoride on the immune system. Damage to immune function seriously affects the quality of life of fluoride-exposed populations and increases the incidence of infections and malignant tumors. Probing the mechanism of damage to immune function caused by fluoride helps identify effective drugs and methods to prevent and treat fluorosis and improve people's living standards in fluorosis-affected areas. Here, the recent literature on the effects of fluoride on the immune system is reviewed, and research on fluoride damage to the immune system is summarized in terms of three perspectives: immune organs, immune cells, and immune-active substances. We reviewed that excessive fluoride can damage immune organs, lead to immune cells dysfunction and interfere with the expression of immune-active substances. This review aimed to provide a potential direction for future fluorosis research from the perspective of fluoride-induced immune function impairment. In order to seek the key regulatory